Analsis Penentuan Dan Strategi Pengembangan Hortikultura Ramah Lingkunga Di Provinsi Kalimantan Barat - Eva Dolorosa, Fanty Maulida, Erlinda Yurisinthae, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
The purposes of this research are: 1. To determine wich one of horticulture national competitive commodity that have potential to be developed in West Kalimantan Province. 2. To analyze sustainable development strategy of national competitive commodity in West Kalimantan Province.This is a decriptive research with survey method and was conducted during 1 year period. Sample was obtained by using purposive smpling method (determining or selecting respondents deliberately). Respondents were selected with consideration of their knowledge, ability and experience in horticulture development. The analysis were Location Quotient, External Factor Evaluation Matrix (EFE), Internal factor evaluation matrix (IFE) and SWOT.Based on LQ calculations, horticulture national competitive commodity that could be developed in West Kalimantan: 1). Vegetables, such as: chilli, cayenne pepper, 2). Fruit such as: banana, orange, durian, 3). Floriculture such as: orchids,4) Rhizome such as :ginger, kencur, galangal.SWOT analyst Results obtained four (4) main strategy of environmental friendly horticultural commodities development in West Kalimantan province, such as: 1). Vegetable Commodities: GAP Training program, GHP-oriented to cultivation and quality of post harvest with Environment friendly practice. 2). Fruits commodity: training program of recycled practice. 3) orchids Commodities: post-harvest coaching program / environmental friendly Orchid products processing. 4). Commodities rhizomes: farmers technical skills development program.Keywords : Horticulture, environmental friendly agriculture, Location Quotient, SWOT